Analisis Maqāṣid Al-Sharī'ah Terhadap Tradisi Buang Bayi Akibat Kesamaan Weton - Evi Erlita Sulistyo Wati; Agus Mahfudin (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
The tradition of symbolic infant disposal due to the similarity of weton (Javanese birth calculation) with parents remains practiced by some communities in Pakis Village, Trowulan District, Mojokerto Regency. This tradition is believed to prevent misfortune that may arise from the similarity of weton between parents and children. This study aims to analyze the practice of the tradition and examine it through the perspective of maqāṣid al-sharī‘ah, particularly the principles of ḥifẓ al-nafs (protection of life) and ḥifẓ al-nasl (protection of lineage). This research employed a qualitative field study approach. Data were collected through interviews, observations, and documentation and analyzed descriptively. The findings reveal that the tradition is merely symbolic and does not constitute child abandonment. The infant is temporarily placed outside the house and then taken back as a symbol of rejecting misfortune. From the perspective of maqāṣid al-sharī‘ah, the tradition may be tolerated as long as it does not endanger the child’s physical or psychological well-being, does not create stigma toward the child, and does not contain elements of shirk. Therefore, the tradition may be preserved as part of local culture while maintaining the Islamic principles of protecting life and lineage.